Introduction to Geography Applications and Websites as Learning Support for Students - M Rizqon Al Musafiri; Faiqotur Rizkiyah (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
This community service aims to enhance the geospatial technology competencies of Geography Education students at the University of Jember through Web-based Geographic Information System (WebGIS) training. The training focused on four main geospatial tools: Google Earth Engine for satellite imagery processing, Caltopo for topographic mapping, Windy.com for real-time meteorological data access, and ArcGIS Online for comprehensive spatial analysis. Using participatory training methods, 30 students participated in the program through presentation, demonstration, and hands-on practice sessions. Results showed significant improvement in students' understanding and skills, with pre-test scores averaging 45.3 increasing to 82.7 in post-tests. The training successfully equipped future geography teachers with essential digital literacy and geospatial analytical capabilities needed for 21st-century geography education. This program contributes to strengthening geography education quality and preparing competent educators capable of integrating geospatial technology in their teaching practice.